2013
DOI: 10.1111/bjet.12118
|View full text |Cite
|
Sign up to set email alerts
|

Self‐regulated learning ability of Chinese distance learners

Abstract: This study reports on self‐regulated learning (SRL) of Chinese distance learners by using a structured SRL scale. SRL of adult and lifelong learners is a well‐researched area, though its application within distance education is a new area of investigation. Open and distance learning lean heavily on self‐learning and self‐learning resources, though interaction at designated learning centers and online learning platforms is occasionally offered. In China, there is still persistence of the age‐old teacher‐centric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 20 publications
1
10
0
2
Order By: Relevance
“…As can be seen from the study of Celik (2012), it was found out that the prospective teachers who graduated from general high schools were more selfregulated than the ones graduated from Anatolian Teacher Trainer High Schools, which was also a result of this study. In line with our findings, Zhao, Chen and Panda (2014) determined that graduates of vocational secondary education institutions were more self-regulated than other high school graduates. The reasons behind these differences among secondary education institutions are beyond the scope of this research; therefore, further studies regarding this issue can be conducted.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 91%
See 1 more Smart Citation
“…As can be seen from the study of Celik (2012), it was found out that the prospective teachers who graduated from general high schools were more selfregulated than the ones graduated from Anatolian Teacher Trainer High Schools, which was also a result of this study. In line with our findings, Zhao, Chen and Panda (2014) determined that graduates of vocational secondary education institutions were more self-regulated than other high school graduates. The reasons behind these differences among secondary education institutions are beyond the scope of this research; therefore, further studies regarding this issue can be conducted.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 91%
“…Wolters and Pintrich (1998) found that gender did not lead to a difference in SRL. Pintrich and de Groot (1990) found that male students had higher self-efficacy perceptions than females, whereas Zhao, Chen and Panda (2014) found that male students were more self-regulated than females. In this context, the findings of this study are consistent with the findings of Turan ( 2009), Caprara et al (2008) and Zimmerman and Martinez Pons (1990).…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 98%
“…Learner-oriented resource design should get more attention in the Chinese culture where teacher-centered instructions have been traditionally mainstreamed. As pointed out earlier in this paper, the recent Chinese policy change toward converting the existing radio and television universities to open universities in some instances (as in the case of BJOU) and to dual mode universities (Wei, 2010) shall demand from students more self-regulated learning abilities (Zhao, Chen, & Panda, 2012) and require distance teachers to look forward to appropriate and sustainable OERs in place of developing self-learning materials (the latter though has not been encouraging in the past).Teachers are not only users of current OER but also willing to make some contributions. From the learners' point of view, Conole and Ehlers (2010) also pointed out that:…”
Section: Discussionmentioning
confidence: 83%
“…Quanto ao gênero, apenas para a dimensão Planejamento SRL foi possível inferir que há diferença estatística de médias, no qual as mulheres utilizam mais estratégias que os homens, corroborando parcialmente os estudos do Valle et al (2008), Zhao et al (2014). Vale mencionar que o estudo Lima Filho, Lima e Bruni (2015) encontrou o mesmo achado, considerando o ensino presencial.…”
Section: Convergênciaunclassified